Rekonstruksi Pemahaman Hadis dan Sunnah Menurut Fazlur Rahman - Zakiyah, Zakiyah; Saputra, Edriagus; Alhafiza, Rahma Ghania (Universitas Islam Negeri Imam Bonjol Padang, 2020)
This article aims to reveal Fazlur Rahman's thoughts about hadith and sunnah. His view of the hadith originated from the controversy in understanding the hadith by the Orientalist. According to the Orientalist, the Hadith lies Muslims in the first century of the emigration and not the words, deeds and decrees of the Prophet. Thus, it is their words that were based on the Prophet Muhammad. A literary survey was used to find out Fazlur Rahman's thoughts. It was carried out by tracing some of Fazlur Rahman's works or articles that discussed Fazlur Rahman's and Orientalist thoughts on the hadith. Thus it was found that the hadith according to Fazlur Rahman related to his rebuttal to Orientalist thought is a hadith originated from the Prophet and not the result of the fabrication of the early Muslim period. Meanwhile, the concept of sunnah which was stated by the Orientalists was considered invalid, because according to them, sunnah was a valid concept and operative since the beginning of Islam. It is valid for all time.